Pemberdayaan Masyarakat Perspektif Maqosid Syariah Pada Masjid KH. Muhammad Sajid Kabupaten Kutai Kartanegara Kalimantan Timur - Adawiyah, Rabiatul; Abdullah, Rais; Gafur, Abdul (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This research aims to analyze community empowerment in a mosque based on the perspective of Maqosid Syariah. This study uses a single case study at a mosque, specifically KH. Muhammad Sajid Mosque. Several mosque administrators and the congregation became informants to understand the concept of empowerment in this mosque. This study formulates Maqosid Sharia-based empowerment that contains religious and spiritual values as a form of devotion oriented to God to create and distribute welfare and added value to the congregation, administrators, community, and surrounding environments. This research will integrate empirical data on empowerment with Maqosid Sharia concepts and theories. This concept can be applied to empowerment practices in various syariah-based social organizations. The concept of Maqosid Syariah-based Empowerment is a concept that is unique to syariah/Islamic social organizations in society, such as mosques, and zakat institutions, along with others.